2020
DOI: 10.1038/s41401-020-00556-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SARS-CoV-2 entry inhibitors among already approved drugs

Abstract: To discover effective drugs for COVID-19 treatment amongst already clinically approved drugs, we developed a high throughput screening assay for SARS-CoV-2 virus entry inhibitors using SARS2-S pseudotyped virus. An approved drug library of 1800 small molecular drugs was screened for SARS2 entry inhibitors and 15 active drugs were identified as specific SARS2-S pseudovirus entry inhibitors. Antiviral tests using native SARS-CoV-2 virus in Vero E6 cells confirmed that 7 of these drugs (clemastine, amiodarone, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 43 publications
(34 reference statements)
4
71
0
Order By: Relevance
“…Although we did not address the mechanism of action, our data on the effect of chlorpromazine on HEK cells and Calu-1 cells are in agreement with these earlier studies. Other antipsychotics, flupenthixol and pimozide, identified as inhibitors of pseudotyped viral infection of HEK cells in our study, have also been confirmed by others as antiviral agents (Drayman et al, 2020;Yang et al, 2020). Pimozide, tested by computational docking analysis and in vitro assays, has been suggested to inhibit main protease of SARS-CoV-2 (M Pro ) (Vatansever et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although we did not address the mechanism of action, our data on the effect of chlorpromazine on HEK cells and Calu-1 cells are in agreement with these earlier studies. Other antipsychotics, flupenthixol and pimozide, identified as inhibitors of pseudotyped viral infection of HEK cells in our study, have also been confirmed by others as antiviral agents (Drayman et al, 2020;Yang et al, 2020). Pimozide, tested by computational docking analysis and in vitro assays, has been suggested to inhibit main protease of SARS-CoV-2 (M Pro ) (Vatansever et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…Recently, a number of studies presented evidence supporting the effects of antidepressant drugs and related psychoactive drugs as antiviral compounds against SARS-CoV-2 (Carpinteiro et al, 2020;Drayman et al, 2020;Hoertel et al, 2021;Lenze et al, 2020;Marion Plaze et al, 2020;Schloer et al, 2020;Yang et al, 2020;Zimniak et al, 2021). One of these studies addressing SSRIs for their antiviral activity did not show any effect of escitalopram and paroxetine, while fluoxetine was successful with inducing antiviral activity after 3 days of treatment (Zimniak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 190 Similarly, other entry inhibitors have been identified from generic screens of approved drugs ( vide infra ), including clemastine, amiodarone, trimeprazine, busitinib, toremifene, flupenthixol, and azelastine, likely via histamine receptor antagonism. 191 Last, owing to the now established role of the integrin α5β1 as a ligand for the spike protein and for ACE2, efforts to interrupt those interactions represent another strategy for inhibiting viral entry. To this end, the integrin-binding peptide, ATN-161, has recently been shown to inhibit these critical interactions in early infection.…”
Section: Translating To Therapies For Sars-cov-2mentioning
confidence: 99%
“…Recently, molecular docking and simulation studies have also reported that azelastine has optimal features for binding with the main protease on SARS-CoV-2 [ 28 ]. Antihistamines trimeprazine, azelastine, and clemastine have been identified as SARS-CoV-2 entry inhibitors following an antiviral test using native SARS-CoV-2 virus in Vero E6 cells [ 36 ]. This suggests that antihistamines have the potential to inhibit SARS-CoV-2 entry into cells.…”
Section: Discussionmentioning
confidence: 99%